Pengaruh Return On Asset, Earning Per Share dan Price To Book Value Terhadap Harga Saham: Studi pada Perusahaan LQ45 yang Terdaftar Di Bursa Efek Indonesia - Fadhil, Aqilah Al Afif (Lembaga Publikasi Ilmiah Nusantara, 2023)
This study aims to examine the effect of Return on Assets (ROA), Earnings per Share (EPS), and Price to Book Value (PBV) on stock prices. The sample consists of companies included in the LQ45 index and listed on the Indonesia Stock Exchange. The sampling technique employed was purposive sampling, which selects samples based on predetermined population characteristics. The research sample comprised 32 LQ45 companies listed on the Indonesia Stock Exchange during the 2016–2020 period. This study utilized secondary data in the form of companies’ financial statements, with data collected through documentation techniques. The data analysis method applied was multiple linear regression analysis, supported by classical assumption tests. The results indicate that Return on Assets (ROA) has a negative and insignificant effect on stock prices, Earnings per Share (EPS) has a positive and significant effect on stock prices, and Price to Book Value (PBV) has a negative and insignificant effect on stock prices. In conclusion, Earnings per Share (EPS) has a positive and significant effect on stock prices, while Return on Assets (ROA) and Price to Book Value (PBV) have negative or insignificant effects on stock prices.